Revolutionizing industry: the path to sustainable manufacturing - G. Pungle, Ramesh (International Journal of Engineering and Technology, 2024)
In the Industrial Revolution, manufacturing has been a cornerstone sector. With each industrial revolution, the focus has been on optimizing the utilization of resources, including manpower, machinery, and materials. Industries aim to enhance manufacturing efficiency to meet societal demands, increase profitability, advance technology, and maintain product quality and variety. This paper illuminates the transitions from Industry 1.0 to 5.0, highlighting technological advancements, benefits, and challenges. Challenges encompass adverse environmental impacts, extensive consumption of natural resources for energy, escalating industrial waste, and an imbalanced industrial ecology. Furthermore, this paper delves into the domain of sustainable manufacturing, tracing its evolution across the industrial revolutions. It elucidates how sustainable manufacturing has emerged as a pivotal concept, grounded in industrial ecology principles and the circular economy. These complementary components are instrumental in promoting not only sustainable manufacturing practices but also sustainable development on a broader scale. Through an in-depth examination, this paper aims to separate out the intricate relationship between these concepts, providing insights into their significance and potential to foster a more environmentally conscious and resilient industrial landscape.